Assembling silicon quantum dots into wires, networks and rods via metal ion bridges. Issue 16 (11th April 2018) - Ohata, Yuki; Sugimoto, Hiroshi; Fujii, Minoru
Abstract : Wires, networks and rods of Si quantum dots (QDs) are produced by bridging Si QDs with metal ions and the electrical properties are studied. Abstract : Wires and networks of Si quantum dots (QDs) with a length of over 1 μm and a width of ∼30 nm are produced by bridging Si QDs with metal ions in solution. It is shown that the width of the wires is almost independent of the preparation parameters and is always about 30 nm, except for the case when Si QDs larger than 30 nm are used, while the length of the wires depends strongly on the kinds of ions, the amount of ions and the amount of Si QDs in a solution. In addition to the microscopic size assemblies, macroscopic size rods of Si QDs with a width of ∼20 μm are produced by using Zn 2+ ions. The XPS analyses reveal that Si QDs are connected to each other via a ZnO layer in the rod. The rods have much higher conductivity and photo-response than Si QD solids produced without metal ions.